Smart tourism – city tourism radar : a tourism monitoring tool at the city of Lisbon - Bernardo, Ana Filipa Marques de Lobão (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence